Green Public Procurement : An Overview of Green Reforms in Country Procurement Systems - World Bank (World Bank, Washington, DC, 2021)
This report provides an overview of international experience in the implementation of Green Public Procurement (GPP). It focuses on the institutional framework that is needed to support the mainstreaming of GPP practices across government. The intention is to equip practitioners with a broad understanding of the issues they need to consider in the design and implementation of GPP reforms. The report draws on a wide range of country examples. It provides links to handbooks and tools for practitioners.